ALCOHOL AND HEART RHYTHM DISORDERS - A. O. Yusupova; A. S. Lishuta (Рациональная фармакотерапия в кардиологии, 2015)
Alcohol abuse and particularly extension of alcohol consumption in alcohol diseas increases the risk of cardiac arrhythmias development and aggravates existing arrhythmias. Patients do not always receive the necessary specific treatment due to lack of detection of the ethanol genesis of these arrhythmias. Management of patients with alcohol abuse and alcohol dependence, including its cardiac complications among other cardiac arrhythmias should use both antiarrhythmic and anti-alcohol drugs and antidepressants. Such issues as diagnosis and management of patients with alcohol-induced cardiac arrhythmias are presented.